The impact of management overconfidence on the risk of stock price crash -- Evidence from Chinese listed companies - WANG, SHURONG (2022)
From the perspective of behavioral finance, this paper discusses whether the overconfidence of managers will aggravate the risk of stock price collapse of listed companies based on the assumption of "incomplete rationality". In addition, this paper further examines whether the relationship between managers' overconfidence and the risk of stock price crashes will change under different property rights and whether the degree of equity concentration will regulate the relationship between the two. In view of the above three problems, this paper takes Chinese A-share listed companies as the research object, selected the 2011-2020 Shanghai and Shenzhen listed companies’ data as samples, and after screening and processing, obtained a total of 15,528 practical observation values. Based on behavioral finance theory, principal-agent theory, information asymmetry theory, and high ladder team theory, the regression models are built drawing from existing literature and empirically verified the above three research assumptions by uni-variate test, correlation analysis, and regression analysis.